2006
DOI: 10.1063/1.2177361
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterizations of iodine molecular wires formed inside the one-dimensional channels of an AlPO4-5 single crystal

Abstract: A uniform array of one-dimensional molecular iodine wires is fabricated by introducing iodine molecules into the channels of AFI zeolite crystals through the vapor phase. The only possible wire structures are formed by linking individual iodine molecules along intramolecular bond axis into a single line. Polarization dependence of Raman intensity at modes of iodine species indicates that the wires are aligned perfectly along the c axis of AFI crystal. Polarized optical absorption as well as resonant Raman scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 18 publications
7
50
1
Order By: Relevance
“…Under the optical microscope with white linearly polarized light, no obvious optical anisotropy was observed. Ye et al [19] reported that the iodine-loaded AlPO 4 -5 crystal was optically isotropic when the iodine density was relatively low inside the channels, while it was optically anisotropic when the iodine density became higher. We can infer that in our situation insufficient iodine is loaded for observing the optical anisotropy.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Under the optical microscope with white linearly polarized light, no obvious optical anisotropy was observed. Ye et al [19] reported that the iodine-loaded AlPO 4 -5 crystal was optically isotropic when the iodine density was relatively low inside the channels, while it was optically anisotropic when the iodine density became higher. We can infer that in our situation insufficient iodine is loaded for observing the optical anisotropy.…”
Section: Resultsmentioning
confidence: 98%
“…Molecular iodine is an interesting Raman laser material, as it has a narrow Raman line width [16] and large output wavelength spectrum [17], and highly efficient I 2 Raman laser was also reported [18]. There are several reports on the inclusion of iodine in the channels of zeolite [19][20][21][22]. I 2 molecules that stabilized in the channels of zeolite have the perspective to realize Raman laser.…”
Section: Introductionmentioning
confidence: 96%
“…53 Raman spectroscopy turned to be very sufficient also for structural characterization of iodine and singlewall carbon nanotubes formed in the channels of AlPO-5 zeolite single-crystal. [54][55][56] 4. Perspectives…”
Section: Zeolite-based Nanocompositesmentioning
confidence: 99%
“…[43][44][45][46][47][48][49] Another advanced application of Raman spectroscopy is the characterization of nanocomposites of carbon and metal-oxide wires and clusters encapsulated into the porous system of a zeolite-type host. [50][51][52][53][54][55][56][57] Visible/near-visible (optical absorption and laser-induced luminescence) spectroscopy, which probes valence-electron states, is an excellent tool to distinguish between cations in oxidation state and sub-nanometric metal-oxide clusters embedded into the framework of nanoscale porous materials. 10,17,33,50,51 The utilization of these spectroscopic methods for structural analysis is often hindered from the broad width and the overlapping of spectral signals; however, the combination of visible/ near-visible spectroscopy with vibrational and/or NMR spectroscopy is beneficial for characterization of photoactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Recently, it was demonstrated that neutral iodine molecules can be loaded into zeolite crystals to form single-molecule wires along the channels. 7,8 Furthermore, one can also precisely control the spatial orientation of neutral iodine molecules in the elliptical channels of AlPO 4 -11 ͑AEL͒ crystals. 9 But it remains little known how these atoms and molecules interact with the zeolite crystal pore structures.…”
mentioning
confidence: 99%